Teenage Sexting and its Consequences - Philip, Ether Lengkat (NIU Journal of Humanities, 2021)
The paper examined the consequences of sexting on the teenagers. Since SEXTING is a contraction of SEX and TEXTING (sending messages of a sexual nature basically through technological advancement of means of communication, such as the use of smartphones). The paper therefore, examined the concepts, the causes, perceptions, consequences and the ways forward. It was however suggested that the stakeholders in health, education and communication Technology should provide more educational interventions on the SEXTING, in order to eradicate all forms of sexual abuse among the teenagers at the global level. The efforts will ameliorate the existing sexting consequences among the teenagers. Keywords: Consequences, Teenage and sexting.